Lifetime Attributable Risk in Mammography Screenings in Dubai: The Influence of Breast Thickness and Age on Radiation Exposure - Kaltham Abdulwahid Mohd Noor; Norhashimah Mohd Norsuddin; Iza Nurzawani Che Isa; Muhammad Khalis Abdul Karim (Diagnostics)
Background/Objectives: This study investigated the lifetime attributable risk (LAR) of radiation-induced breast cancer from mammography screening in Dubai. It aimed to explore the relationship between breast thickness, patient age, and the associated radiation dose during mammographic examinations. Methods: A retrospective analysis was conducted on 2601 patients aged 40 to 69 across five screening facilities in Dubai’s healthcare system. Due to a low correlation between the mean glandular dose (MGD) and breast thickness, both glandular and non-glandular doses were included in calculations as the organ dose (OD). This comprehensive approach examined the impact of whole breast tissue on risk assessments. Key exposure parameters such as the kilovoltage peak (kVp), milliampere-seconds (mAs), and source-to-skin distance were extracted from the dose survey. Results: Our findings reveal that the organ dose increases with breast thickness, emphasizing the need for dose optimization in denser tissues. The LAR decreases with age across all thickness categories, but higher initial LAR values were seen in younger patients with thicker tissue. This study emphasizes the increased sensitivity of younger women, who usually have denser breast tissue, to radiation-induced cancer risks. Conclusions: Personalized screening protocols considering age and breast thickness are crucial for balancing early cancer detection benefits with radiation risks. Future research should improve mammography protocols, explore alternative methods, and consider generic testing for young high-risk patients to mitigate risks while maintaining diagnostic efficacy.